Hubungan Paparan Pornografi Melalui Media Massa dengan Perilaku Seksual Remaja di SMA Negeri 2 Surakarta - Ismanuworo, Agung; Suparman, .; Wijayanti, Lilik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Adolescent marked with the unbalanced physical and mental growth which is followed by behaviorally trying something often lead into sex before marriage, unwanted pregnancy, unsave abortion and sexually transmitted disease. While in Surakarta itself, about 30,09% high school male adolescents have ever done a sexual intercourse and 5,33% among them are female adolescents. This research aims to find the association between pornography exposure and adolescent sexual behavior as the first step to decrease its number. Methods: Located in SMA Negeri 2 Surakarta, this research use cross sectional method with 103 responders taken by simple random sampling and analyzed bivariatly with Chi Square. The independent variable is pornography exposure in mass media and the dependent variable is adolescent sexual behavior. Results: There were 57 students (55,34%) exposed to pornography for the last month, meanwhile the other 46 students (44,66) weren?t exposed to pornography for the last month. There were 21 students (20,39%) who had bad sexual behavior, meanwhile the rest 82 students (79,61%) had good sexual behavior. There were 16 students (15,53%) who had been exposed and had bad sexual behavior. But, there were 5 students (4,85%) who weren?t exposed yet had bad sexual behavior. Conclusions: Using Chi Square, it can be concluded that there?s a meaningful association between pornography exposure and sexual behavior. Keywords: adolescent, media, pornography, sexual behavior